Chiral chromane[4]arenes synthesised by cycloaddition reactions of o-quinomethine resorcin[4]arenes. (22nd January 2019) - Stefańska, Karolina; Szafraniec, Anna; Szymański, Marek P.; Wierzbicki, Michał; Szumna, Agnieszka; Iwanek, Waldemar
Abstract : The synthesis of cavity-extended cyclochiral heterocyclic derivatives of chromane[4]arenes by a cycloaddition reaction between the o -quinomethine derivative of resorcin[4]arene and various styrenes is described. Abstract : We present the synthesis of chromane[4]arenes – cavity-extended inherently chiral heterocyclic derivatives of resorcin[4]arenes – by the Diels–Alder reaction between the o -quinomethine derivative of resorcin[4]arene and various styrenes. Among many possible stereoisomers of chromane[4]arenes, only C 4 -symmetric stereoisomers (as two diastereoisomers) are formed selectively in 44–88% yield and up to 90% de. The structures were analysed by NMR, X-ray crystallography and circular dichroism. Chromane[4]arene derived from 4-methylstyrene forms mixed crystals with all four stereoisomers present in the crystal lattice in a non-statistical ratio (60 : 40). Diastereoisomeric molecules occupy the same position in the asymmetric unit and their different configurations are manifested as a partial disorder. Stereoisomers were separated by HPLC coupled with an ECD detector and their ECD spectra were recorded. The spectra were compared with theoretical ECD spectra (TD-DFT method). The results indicate that the signs and shapes of the ECD spectra are mainly determined by the inherent chirality of the resorcin[4]arene scaffolds, while the configurations of the stereogenic centers at the upper rim have a minor effect.